Mirror symmetry and conformal flatness in general Relativity. (1st September 2004) - Gravel, P.; Gauthier, C.
Abstract : Using symmetry arguments only, we show that every spacetime with mirror-symmetric spatial sections is necessarily conformally flat. The general form of the Ricci tensor of such spacetimes is also determined.